(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Despite the commitments assumed and health`s declarations made in the last 80 years; it is a fact recognized by the international organizations that health equity still remains to be achieved in the majority of countries. In addition, there is a lack of agreements in order to define and advance towards systemic policies that can achieve this challenge. During the course of this 21st century, we have witnessed a global COVID-19 pandemic, the return of illness that we believed were already controlled such as Ebola, the progressive threat of environmental problems, the increasing bacterial antimicrobial resistance or the exponential growth of chronic pathologies; all challenges that forces us to make urgent decisions aimed to reorganize the existence of a global health system. As a contribution to a necessary and urgent debate in this sense, this document presents contributions on complexity theories that might be useful for the integration and optimization of the current health model.